Two inertial subgradient extragradient algorithms for variational inequalities with fixed-point constraints. (3rd June 2021) - Ceng, L. C.; Petruşel, A.; Qin, X.; Yao, J. C.
Abstract : This article proposes two general inertial algorithms with line-search process for finding a solution of a variational inequality problem with fixed-point constraints via a subgradient-extragradient approach. Common solution theorems are obtained in Hilbert spaces.